Code commentation and code documentation practises for FTMSK's web portal / Mohd Hafzam Mohd Zin - Mohd Zin, Mohd Hafzam (2005)
Code commentation and code documentation practises developed professionally to support continuous maintenance for a source code of a software system. By applying these practises, hopeftilly software maintenance becomes easier. This project reports results obtained from the implementation of these practises which are strongly suggest that the activities are convenient. The results show clear advantage of having standard style of comments which could help programmer to understand code faster for future use. The results fiorther show the steps to make coding standardized, by using several approaches and programming techniques. Code documentation generated using auto-documentation generator which reads comments written in the source code with standard style of comment. All steps regarding these practises are provided to help programmer understand the conceptual approach and implementation approach. As an example, a group of codes is commented and documented using these approaches.